INTEGRASI KURIKULUM PENDIDIKAN MULTIKULTURAL DALAM MEWUJUDKAN TOLERANSI DAN KEHARMONISAN SOSIAL DI SDN 01 PATOMAN - Dhevy Ratna Sari; Rifkian Kurniawan; Erna Yayuk (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the form, function, and meaning of multicultural education curriculum integration in realizing tolerance and social harmony at SDN 01 Patoman. The background of this study is the importance of multicultural education in elementary schools to instill values of tolerance, mutual cooperation, and respect for differences. The research used a descriptive qualitative approach with 12 subjects consisting of the principal, teachers, and students. Data were collected through observation, interviews, and documentation and analyzed using an interactive model that included reduction, presentation, and conclusion drawing. The results of the study show that the integration of multicultural education at SDN 01 Patoman is realized through two main forms, namely integration in thematic learning and strengthening the attitude of respecting differences among students. The function of this integration includes the formation of tolerant and inclusive attitudes through a contextual pedagogical approach that is relevant to the lives of students. The meaning of multicultural curriculum integration is evident in the creation of a harmonious and diversity-friendly school culture, where all members of the school community can live together peacefully without discrimination. This study confirms that the consistent application of multicultural values in the curriculum and the support of an inclusive school environment are key factors in shaping students' tolerant, empathetic, and patriotic character.